PERCEPTION OF CLASS VIII STUDENTS ON THE IMPLEMENTATION OF A SCIENCE LEARNING PROCESS BASED ON CURRICULUM 2013 SMPN 2 LENGAYANG - Destaria Sudirman; Rivo Juita Sudirman (Jurnal Ilmu Pendidikan Ahlussunnah, 2023)
Curriculum 2013 is a curriculum that emphasizes the modern pendagogik dimension of learning is to use a scientific approach. The learning process is based on the curriculum in 2013 in five core activities consist of the following principal activities of the learning experience to observe, ask, gather information, associates, and communicate. Curriculum 2013 aims to strike a balance between knowledge, attitudes, and skills for learners. The purpose of this study is to determine how students' perceptions of Class VIII of the implementation of the learning process based on the IPA curriculum in 2013 SMPN 2 Lengayang. This research is descriptive data obtained through questionnaires (questionnaires) were given to students of VIII SMPN 2 Lengayang. The sampling technique used was cluster random sampling technique. where each class is taken 30% of the total number of students. The data obtained were processed using techniques percentage (%). Based on the analysis of data obtained from the research is that students' perceptions of class VIII on the implementation of the learning process based on the biology curriculum in 2013 SMPN 2 Lengayang as a whole is simply the percentage that is equal to 77,09%. Of the five activities in the learning process based on the curriculum of 2013, there are two categories: good and sufficient. Where that has both categories, namely the activities of observed and which have enough category on the activity ask, associate, collecting and communicating information.